PENERAPAN MODEL PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION (GI) DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS X SMK N 1 MONDOKAN SRAGEN - Nurmawan, Wahid (Jurnal Nosel, 2013)
The objectives of this research will be : (1) improving the student activity in learning by using Cooperative Learning Group Investigation Model in Vocational Basic Competence Lesson of Light Vehicle Automotive  Engineering; (2) understanding the result of teaching learning by using Cooperative Learning Group Investigation Model. This study was a classroom action research method which this research was implemented in two cycles, each cycle consisting of four stages, namely the planning stage, the action stage, the observation stage and reflection phase. Subjects of research were students of tenth grade level in SMK Negeri 1 Mondokan Sragen. The data were collected from teacher and students. The techniques of collecting data that the author used were observation, interview and test. The validity of data used the triangulation of sources. The data were analyzed by using descriptive comparative and analytic of qualitative data. The result of this research showed that the use of cooperative learning group investigation model could improve student of activity and the result of learning in cooling technique learning. It could be seen by the increasing student activity and the result of learning in each cycle. At the initial value average,  the average activity is 20.17% and the average learning result is 57.18. After the first cycle of action, student activity increased to 56.53%  and average learning result increased to 69.68. While the second cycle, student activity increased to 80.11% and average learning result increased to 77.97.